Enhancing the Pharmacological Properties of Triterpenes Through Acetylation: An Anticancer and Antioxidant Perspective - Barbara Bednarczyk-Cwynar; Piotr Ruszkowski; Andrzej Günther; Szymon Sip; Katarzyna Bednarek-Rajewska; Przemysław Zalewski (Molecules, 2025)
This paper presents the influence of acetylation on the cytotoxic and antioxidant activity of natural triterpenes. Oleanolic acid, betulin, betulinic acid and other triterpenes have been modified to improve their pharmacological properties. Acylation of the hydroxyl group at the C-3 position showed significant changes in biological activity, in particular against cancer cell lines such as HeLa, A-549, MCF-7, PC-3 and SKOV-3, with the highest IC50 results for acetyloleanolic acid (1b) and acetylbetulinic acid (4b). Docking results showed that all compounds tested demonstrated the ability to bind to pockets (C1–C5) of the p53 Y220 protein, obtaining different Vina score values. The strongest binding was observed for compound 2b in the C3 pocket (−10.1 kcal × mol−1), while in the largest C1 pocket, the best result was achieved by compound 5b (−9.1 kcal × mol−1). Moreover, antioxidant studies using the CUPRAC and DPPH tests showed significant differences in the mechanisms of action of the compounds depending on the structure. The analyses of ADMETox confirmed the favorable pharmacokinetic profile and low toxicity of most of the tested derivatives. The results suggest that acetylated triterpenes, especially 1b and 4b, have great potential as anticancer drug candidates, requiring further research on their cytotoxic activity and structural modifications.